Word of honor - Demille, Nelson (New york Warner, 1985)
"This book is the personal memoir of protagonist Peter Wake, a veteran of espionage operations for the Office of Naval Intelligence who also has considerable sea and combat experience. At the beginning of this book, it is three years after the war and Wake is called in to explain his decisions and actions in the Caribbean during the wartime summer of 1898"
1 4
Keywords: English Fiction